2001
DOI: 10.1075/gest.1.1.06kit
|View full text |Cite
|
Sign up to set email alerts
|

Pointing left in Ghana

Abstract: In Ghana, many peolple consider pointing by the left hand to be a taboo. We investigated consequences of this taboo on the Ghanaian gestural practice by observing gestures produced during naturalistic situations of giving route directions. First, there is a politeness convention to place the left hand on the lower back, as if to hide it from the interlocutor. Second, as a consequence of left-hand suppression, right-handed pointing may involve an anatomically staining position when indicating a leftward directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Universality: Speech-accompanying gesture is a cross-cultural universal (Iverson & Thelen, 1999;Kita & Essegbey, 2001;McNeill, 1992;Núñez & Sweetser, 2001). 2.…”
Section: How Can Aymara Speakers' Gestures Help Usmentioning
confidence: 99%
“…Universality: Speech-accompanying gesture is a cross-cultural universal (Iverson & Thelen, 1999;Kita & Essegbey, 2001;McNeill, 1992;Núñez & Sweetser, 2001). 2.…”
Section: How Can Aymara Speakers' Gestures Help Usmentioning
confidence: 99%
“…Furthermore, a majority of the people in Ghana (about 60% of the participants interviewed in Kita and Essegbey, 2001) consider pointing gesture with the left hand to be rude and disrespectful towards the addressee. It was investigated how this gesture taboo influenced the use of gestures in naturalistic route descriptions elicited on the street of a southern Ghanaian town.…”
Section: Gestural Politenessmentioning
confidence: 99%
“…Such gestures were inconspicuous due to the size and location, and more importantly, were not considered to be a gesture by Ghanaians for the purpose of the taboo. Because such gestures were often not visible to the addressee, and they tended to appear immediately before or with the description of a left-turn, Kita and Essegbey (2001) suggested that such left-hand gestures may be triggered by cognitive needs to facilitate the speech production when verbally expressing the concept "left" (see, e.g., Kita, 2000;Krauss, Chen, & Gottesman, 2000 for further discussions of self-oriented functions of gesture).…”
Section: Gestural Politenessmentioning
confidence: 99%
“…The words for right in French (droite) and in German (Recht) are closely related to the words meaning "a 'right' or privilege accorded by the law," whereas the words for left in French (gauche) and German (Links) are related to words meaning "distasteful" or "clumsy." Such idioms are evident in nonlinguistic conventions in some cultures, such as Ghanaian society, where pointing and gesturing with one's left hand is prohibited (Kita & Essegbey, 2001). According to Islamic doctrine, the left hand should be used for dirty jobs, whereas the right hand is used for eating.…”
mentioning
confidence: 99%